Rhabdomyoblasts in an Ovarian Cystic Teratoma - Farooq, Hajra; Haque, Anwar Ul (International Journal of Pathology, 2018)
Children with cystadenomatoid malformation of lungs may contain rhabdomyoblasts while occasionally adult lungs may contain rhabdomyoblasts. On the other hand rhabdomyosarcoma have been reported in cystic teratoma of the lung. However benign rhabdomyoblasts are not reported in the benign cystic teratoma. We report such a case here.